Sistem Kontrol dan Pemantauan Budidaya Bayam Secara Hidroponik di Desa Widarapayung Wetan - Erna Alimudin; Arif Sumardiono; Zaenurrohman; Hera Susanti; Fadhillah Hazrina (Politeknik Negeri Cilacap, 2023)
Abstract-Widarapayung Wetan Village is developing a village that applies technology as well as an educational tourism object. Technology tourism combined with agriculture to become modern agricultural tourism. One of the applied agriculture is spinach cultivation so that the results from agriculture can be developed into a food product such as spinach chips. Hydroponic greenhouses that use Internet of Things technology can be used for modern agricultural implementation. Monitoring systems and automatic control systems will be able to assist in the maintenance of spinach cultivation. The application of modern agriculture is expected to add insight to the surrounding community. In addition, the greenhouse with this technology is expected to be an attraction to provide knowledge to visitors and the public as educational and technology tourism. The tour can introduce the planting process, controlling the environment around the plants using sensors and monitored through the website. The stages undertaken include constructing a green house framework, establishing a monitoring system, and placing the greenhouse at the destination location or related partners. In addition, further activities include manufacturing hydroponics, manufacturing and assembling control systems, as well as training on the use and maintenance of hydroponic greenhouses.